Death Audit of Deaths Due to Malaria at Lg Hospital, Ahmedabad (Gujarat) During the Year 2011 - Vyas , Sheetal; Solanki, Anand; Joshi , Urvish; Nayak, Himanshu (National Journal of Community Medicine, 2012)
Context: Approximately half of the world's population is at risk of malaria. Understanding of profile of deaths due to malaria can help in appropriate and early management of cases and thereby reducing mortality in future. Aims: To study the seasonal pattern, profile, survival period, symptoms, signs, and complications, treatment details of malaria death cases and study the facilities for management. Materials and Methods: Information about deaths due to malaria was procured from the indoor case papers of cases from the medical record department of LG hospital from January 2011 to December 2011 and subsequently analysis was done using appropriate statistical software. Results: A total of 32 malaria deaths occurred in the above mentioned period. Overall CFR was 3.4% for indoor malaria cases. Mean age of cases was 42.23 years. There were 53.1% of patients falling in the age group 50 years and above. Out of total deaths, 59.37% were males and 40.63% were females. Twenty (62.5%) cases were positive for Plasmodium falciparum, 8 (25%) case for Plasmodium vivax, and 4 (12.5%) case were having mixed infection. Median survival period was 23.5 hours. The most common presenting symptom was intermittent fever and altered sensorium. All cases were given treatment as per guidelines of National drug Policy on Malaria (2010) immediately after diagnosis. Facility survey revealed all facilities as per recommendation under NVBDCP. Conclusions: Malaria still remains one of the important causes of admission and mortality. Early identification and referral of complicated malaria cases from community to higher health care facilities can reduce the mortality.